Readiness of academic youth to undertake over-personal tasks from the perspective of their family-related experiences - Zofia Remiszewska (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
In my research, I was looking for a connection between readiness to undertake over-personal tasks and family experiences related to the process of education, asking myself the following questions: If the family has an important role in preparing the young person for over-personal tasks? Whether - and if so, to what extent and scope - childhood experiences affect the willingness of young people to undertake over-personal tasks? Because the family experiences study which determined readiness to undertake the over-personal tasks consisted of the presentation of parents' image by the respondents in the context of their educational activities and on determining the type and frequency of disciplinary measures applied to them - I decided to check what predictors arise from the parents' image, and which of the applied disciplinary measures condition the readiness to undertake the over-personal tasks. The applied method of multiple regression analysis allowed to distinguish predictors statistically significant for their relationship with readiness to undertake over-personal tasks. The conducted statistical analysis indicated a significant relationship between the discussed variables.